Mitochondrial‐Mediated Oxidative Ca2+/Calmodulin‐Dependent Kinase II Activation Induces Early Afterdepolarizations in Guinea Pig Cardiomyocytes: An In Silico Study. Issue 15 (7th August 2018) - Yang, Ruilin; Ernst, Patrick; Song, Jiajia; Liu, Xiaoguang M.; Huke, Sabine; Wang, Shuxin; Zhang, Jianyi Jay; Zhou, Lufang
Abstract : Background: Oxidative stress–mediated Ca 2+ /calmodulin‐dependent protein kinase II (CaMKII) phosphorylation of cardiac ion channels has emerged as a critical contributor to arrhythmogenesis in cardiac pathology. However, the link between mitochondrial‐derived reactive oxygen species (mdROS) and increased CaMKII activity in the context of cardiac arrhythmias has not been fully elucidated and is difficult to establish experimentally. Methods and Results: We hypothesize that pathological mdROS can cause erratic action potentials through the oxidation‐dependent CaMKII activation pathway. We further propose that CaMKII‐dependent phosphorylation of sarcolemmal slow Na + channels alone is sufficient to elicit early afterdepolarizations. To test the hypotheses, we expanded our well‐established guinea pig cardiomyocyte e xcitation‐ c ontraction coupling, m itochondrial e nergetics, and R OS‐ i nduced‐ R OS‐ r elease model by incorporating oxidative CaMKII activation and CaMKII‐dependent Na + channel phosphorylation in silico. Simulations show that mdROS mediated‐CaMKII activation elicits early afterdepolarizations by augmenting the late Na + currents, which can be suppressed by blocking L‐type Ca 2+ channels or Na + /Ca 2+ exchangers. Interestingly, we found that oxidative CaMKII activation–induced early afterdepolarizations are sustained even after mdROS has returned to its physiological levels. Moreover, mitochondrial‐targeting antioxidant treatment can suppress the early afterdepolarizations, but only if given in an appropriate time window. Incorporating concurrent mdROS‐induced ryanodine receptors activation further exacerbates the proarrhythmogenic effect of oxidative CaMKII activation. Conclusions: We conclude that oxidative CaMKII activation–dependent Na channel phosphorylation is a critical pathway in mitochondria‐mediated cardiac arrhythmogenesis.